Används ekonomiska planeringshjälpmedel i lantbruksföretag : beslutsunderlag med hjälp av kalkylmetoder - Andersen, Glenn; Jansson, Johan (SLU/Dept. of People and Society, 2010)
In agricultural educations you learn to use different economic planning tools, as basis for decision. The purpose and goal of this work has been to find out if economic planning tools are used by the farmers in Sweden. We choose to do an investigation through personal interviews, and used an inquiry to get as equivalent answers as possible from the farmers.